Preparation and characterization of a high heat resistant phthalonitrile resin modified by polyborosilazane ceramic precursor. (7th March 2022) - Wang, Zi‐long; Han, Yue; Guo, Ying; Ye, Li; Han, Wei‐jian; Zhou, Heng; Wang, Jun; Liu, Wen‐bin; Zhao, Tong
Abstract: Phthalonitrile resins were an important kind of matrix with high thermal stability. Novel organic–inorganic hybrid composites were prepared by employing 4, 4′‐(1, 3‐phenylenebis[oxy]) diphthalonitrile (DPN) modified with polyborosilazane ceramic precursor (PBSN) in this work to explore the methods for synthesis of phthalonitrile resin with good processability as well as high heat‐resistance. The maximal glass transition temperature ( T g ) and 10% weight loss temperatures were about 615.0 and 608.1°C (N2 ), respectively. The detailed thermal oxygen decomposition processes and mechanisms were studied and Avrami‐Erofeev models were used for decomposition kinetic analysis of the hybrid matrix. According to the result of the scanning electron microscope, the PBSN was completely integrated into the phthalonitrile resin, and the heat‐resistant structure (SiO, BN and BO) could improve the heat resistance of DPN. The hybrid matrix could be used for heat‐resistant materials.